Awareness of Sustainable Agriculture among Polish Farmers – Beneficiaries of the CAP - Piotr Sulewski; Adam Wąs (Wieś i Rolnictwo)
The main objective of the study was an assessment of the awareness and actions undertaken by farmers in the selected fields of farm activity from the sustainability point of view. The research covered a representative sample of 600 farmers participating in the Polish Farm Accountancy Data Network (FADN). The data from the FADN database were supplied by the information from interviews with farmers. The sustainability indicators were analysed with regard to the amount and type of subsidies received. The sample was divided regarding type and amount of support. The results showed that, on average, the highest sustainability indicators were in farms receiving support under agri-environmental programmes and located in LFAs (less favoured areas), while the lowest were usually in other farms in the LFAs. The analysis of differences between farms categorised according to the total value of subsidies received, found that on average farms with the highest absolute level of support achieved higher sustainability parameters in all dimensions. Based on the results it can be concluded that higher and more varied subsidies to farmers are positively correlated with sustainability of their farms.